Epidemiology and Visual Outcome of Pediatric Ocular Trauma in a Major Tertiary Eye Center in Tunisia: A 6-Year Retrospective Study - Mohamed Foued Rmili; Ahmed Chebil; Rim Limaiem; Nibrass Chaker; Rym Bouraoui; Yousra Falfoul; Leila El Matri (Journal of Current Ophthalmology)
Purpose: To describe the epidemiological profile, clinical characteristics, and visual outcome of pediatric ocular trauma in Tunisia. Methods: In this retrospective cohort study, we reviewed the charts of 398 children younger than 16 years of age, presenting to the Emergency Department “B” of Hedi Rais Institute of Ophthalmology, for ocular trauma. The study period was between January 1, 2013, and January 1, 2019. The final best-corrected visual acuity (BCVA) was measured at the end of the follow-up period, which was 6 months. We used the Chi-squared test to compare the two groups of final visual acuities (good vs. poor visual outcome) for different prognostic factors. The ocular trauma score (OTS) and the pediatric OTS (POTS) were calculated for each child. We used the Cohen’s kappa coefficient to evaluate the agreement between our final visual acuities using OTS and POTS. Results: The mean age was 7.95 years with a sex ratio (males to females) of 5.32. Closed-globe injury (CGI) was found in 321 eyes, while 101 eyes had open-globe injury (OGI). Injuries were bilateral in 24 children. The majority of injuries occurred at home. The predominant mechanism of injury was fall in CGI and tree branch in OGI. Initial and final BCVA were predominantly ≤0.3 logMAR in both CGI and OGI. OTS category 3 and POTS category 2 were the most common. Factors associated with poor prognosis included delay to consultation >24 h (P = 0.0001); initial BCVA >1 logMAR (P = 0.0001); OGI (P = 0.001); size of injury ≥5 mm (P = 0.01); zone III in OGI (P = 0.032); endophthalmitis (P = 0.001); OTS 1 and 2 (P = 0.01); POTS 1 (P = 0.0001); and the following associated lesions: cataract (P = 0.006), retinal detachment (P = 0.03), and intraocular foreign body (P = 0.03). We found that both OTS (P = 0.001) and POTS (P = 0.003) were predictive of the final BCVA, with a moderate agreement between them (Cohen’s kappa = 0.56). Conclusions: Studying the epidemiological profile and identifying the risk factors for poor visual outcome of pediatric ocular trauma are necessary to implement preventive measures. A thorough clinical evaluation and close patient follow-up are crucial for identifying these risk factors. Both OTS and POTS were predictive of the final visual outcome. POTS has the advantage of bypassing the initial visual acuity which may be difficult to assess in children.